Innovative Culture as the Key to the Success of Electronic-Based Government Systems - Karim, Jorry; A. Hatu, Rauf; Hidayat Koniyo, Moh.; Abdussamad, Zuchri (Iapa Proceedings Conference, 2024)
This study aims to analyze how organizational culture plays a role in successfully implementing the Electronic-Based Government System in Gorontalo Province. Bureaucratic reform through digitalization is the main focus in efforts to improve the quality of public services. However, its implementation faces various internal challenges, such as resistance to change, lack of adequate training, and weak digital infrastructure. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, field observations, and documentation at the Gorontalo Provincial Regional Apparatus Organization. The study results show that an organizational culture that supports innovation and professionalism plays an important role in accelerating the implementation of Regional Apparatus Organizations that implement transformational leadership and have strong cultural values, such as integrity and commitment, show an increase in the implementation of digitalization. However, the decline in scores in 2021 and 2022 indicates resistance to change and a lack of inadequate training and digital infrastructure. This study concludes that the success of implementation does not only depend on the technological aspect, but also on the readiness of organizational culture, employee competence, and leadership support. Strengthening organizational culture, increasing training, and developing better digital infrastructure are key factors to ensure the sustainability of digital-based bureaucratic reform in Gorontalo Province.